2-7. Solve; 2(x-5)+ 3 (x - 2) = 8 + 7 (x-4).
Answers
Answered by
0
Step-by-step explanation:
here is your answer brother
Attachments:
![](https://hi-static.z-dn.net/files/d40/67d4751ec2da201177d7af7d7105c36e.jpg)
Answered by
11
Step-by-step explanation:
2( x -5 ) + 3( X - 2 ). = 8 + 7( X - 4 )
2x -10 +3x -6 = 8 + 7x - 28
5x -16 = 7x -20
4 = 2x
X = 2
hope you understand......
please mark it as brainleist answer......
Similar questions
World Languages,
7 months ago
Social Sciences,
7 months ago
Math,
1 year ago
Sociology,
1 year ago
Economy,
1 year ago
Geography,
1 year ago